The Econometrics of Growth and Underdevelopment: A Test of the Dual Hypotheses - McIntosh, James (Review of Economic Studies, 1978)
Journal Article The Econometrics of Growth and Underdevelopment: A Test of the Dual Hypotheses Get access James McIntosh James McIntosh University of Essex Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 2, June 1978, Pages 285–298, https://doi.org/10.2307/2297344 Published: 01 June 1978 Article history Received: 01 February 1976 Accepted: 01 May 1977 Published: 01 June 1978